2023
DOI: 10.1177/10711007231160751
|View full text |Cite
|
Sign up to set email alerts
|

Association of Talar Neck Fractures With Body Extension and Risk of Avascular Necrosis

Abstract: Background: The objective of this study was to determine whether talar neck fractures with proximal extension (TNPE) into the talar body are associated with higher rates of avascular necrosis (AVN) compared to isolated talar neck (TN) fractures. Methods: A retrospective review of patients sustaining talar neck fractures at a level I trauma center from 2008 to 2016 was performed. Demographic and clinical data were collected from the electronic medical record. Fractures were characterized as TN or TNPE based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…4,6 There is limited research on talar neck fractures combined with talar body fractures. In contrast to our findings, Mechas et al 22 reported a 49% incidence of avascular necrosis in talar neck fractures with proximal extension (TNPE), suggesting a significantly higher rate of complications, including subsequent collapse and non-union, compared to isolated talar neck fractures. In our study, the outcomes for the four cases with TNPE did not exhibit a similar trend.…”
Section: Complications and Functional Outcomescontrasting
confidence: 99%
See 1 more Smart Citation
“…4,6 There is limited research on talar neck fractures combined with talar body fractures. In contrast to our findings, Mechas et al 22 reported a 49% incidence of avascular necrosis in talar neck fractures with proximal extension (TNPE), suggesting a significantly higher rate of complications, including subsequent collapse and non-union, compared to isolated talar neck fractures. In our study, the outcomes for the four cases with TNPE did not exhibit a similar trend.…”
Section: Complications and Functional Outcomescontrasting
confidence: 99%
“…Mechas et al . 22 studied the morphology of central talar fractures, identifying and summarizing talar neck fractures with proximal extension (TNPE). They defined TNPE as a fracture that originates on the talar neck and extends proximal to a line subtended from the junction of the talar neck and the articular cartilage dorsal to the anterior portion of the lateral process of the talus.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of FAI , Mechas et al 3 reported their experience in treating talar neck fractures, describing talar neck fractures with proximal extension (TNPE). This subset of fractures, which extend proximally into the anterior aspect of the talar dome cartilage, occur commonly, and have not been previously characterized.…”
mentioning
confidence: 99%